PELESTARIAN DAN EKSISTENSI TARI TRADISIONAL DI SUMATERA BARAT: TINJAUAN SISTEMATIS - Sonia, Uthi; Astuti, Fuji; Ardipal, Ardipal; Indrayuda, Indrayuda; Yuliasma, Yuliasma (Ensiklopedia of Journal, 2026)
Traditional dance is an intangible cultural heritage that holds significant value in preserving a community's cultural identity. This study aims to systematically analyze literature related to the preservation and existence of traditional dance, focusing on developing preservation strategies through digital technology and educational approaches. The method used is Systematic Literature Review (SLR) following PRISMA 2020 guidelines with article searches from the Scopus database for the period 2020-2025. From 1,111 identified articles, through screening and eligibility assessment processes, 50 articles were analyzed. The analysis results show that traditional dance preservation efforts are developing through four main approaches: (1) utilization of digital technologies such as Virtual Reality, Augmented Reality, and motion capture; (2) integration of dance education in formal curriculum; (3) ontology-based documentation and databases; and (4) revitalization through community participation. 3D technology and artificial intelligence have proven effective in documenting and transmitting traditional dance heritage. This study provides important implications for developing preservation strategies for Pilin Salapan Dance in Nagari Air Bangis, Pasaman Barat Regency, West Sumatra.Keywords: Traditional Dance, Preservation, Intangible Cultural Heritage, Digital Technology, West Sumatra